2011
DOI: 10.1038/jid.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Denervation of Psoriasiform Mouse Skin Improves Acanthosis and Inflammation in a Sensory Neuropeptide-Dependent Manner

Abstract: Nervous system involvement in psoriasis pathogenesis is supported by increases in nerve fiber numbers and neuropeptides in psoriatic skin and by reports detailing spontaneous plaque remission following nerve injury. Using the KC-Tie2 psoriasisform mouse model, we investigated the mechanisms by which nerve injury leads to inflammatory skin disease remission. Cutaneous nerves innervating dorsal skin of KC-Tie2 animals were surgically axotomized and beginning 1d following denervation, CD11c+ cell numbers decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 53 publications
9
124
1
2
Order By: Relevance
“…These data are in agreement with a previous study in which surgical denervation improved skin lesions and inflammation in a mouse model of psoriasis (KC-Tie2). Importantly, a role for SP and CGRP signalling was also suggested in this work 149 . Interestingly, clinical reports show that psoriasis undergoes remission following nerve transection or injury in the context of decreased functioning of the nervous system, a finding that has also been observed in rodent models of the condition [149][150][151] .…”
Section: Modulated Effects Refsmentioning
confidence: 74%
“…These data are in agreement with a previous study in which surgical denervation improved skin lesions and inflammation in a mouse model of psoriasis (KC-Tie2). Importantly, a role for SP and CGRP signalling was also suggested in this work 149 . Interestingly, clinical reports show that psoriasis undergoes remission following nerve transection or injury in the context of decreased functioning of the nervous system, a finding that has also been observed in rodent models of the condition [149][150][151] .…”
Section: Modulated Effects Refsmentioning
confidence: 74%
“…In a genetic mouse model of chronic psoriasiform dermatitis accompanied by enhanced cutaneous innervation, Ward and colleagues showed that surgical denervation ameliorated epidermal hyperplasia and some inflammatory parameters [191]. In this model, Substance P promoted the accumulation of CD11c + leukocytes, CGRP was important for epidermal thickening, and blockade of neuropeptide release by local injection of botulinum neurotoxin could ameliorate disease [191, 192]. …”
Section: Role Of the Pns In Barrier Tissuesmentioning
confidence: 99%
“…In one model, mice are engineered to overexpress the receptor tyrosine kinase Tie2 in keratinocytes (Wolfram et al . 2009, Ostrowski et al . 2011).…”
Section: Calcitonin Gene-related Peptide and Inflammatory Skin Diseasesmentioning
confidence: 99%